1981
DOI: 10.1038/bjc.1981.121
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of prolactin in nulliparous women

Abstract: Summary.-Follicular-phase (Day 11) plasma prolactin, and plasma and urinary oestrogen levels of 70 nulliparous nuns were compared with those of 80 of their sisters, of whom 62 were parous. The nuns and their nulliparous sisters did not differ significantly in their prolactin and oestrogen levels. No differences in plasma oestrogens or urinary oestriol ratio were found between the parous and the nulliparous women. However, the mean prolactin level of the nuns and their nulliparous sisters was 3500 higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 9 publications
5
27
0
1
Order By: Relevance
“…[9][10][11][12][13] Parous postmenopausal women also had significantly lower prolactin levels than nulliparous women, consistent with 2 prior studies, 9,14 though the difference was not as large as among premenopausal women. We did not observe a significant gradient in prolactin concentration with increasing number of children, similar to the results of some 10,11,13 but not all 9,12,14 studies. In one of the studies with an observed gradient, the difference between nulliparous and uniparous was greater than between subsequent number of children.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…[9][10][11][12][13] Parous postmenopausal women also had significantly lower prolactin levels than nulliparous women, consistent with 2 prior studies, 9,14 though the difference was not as large as among premenopausal women. We did not observe a significant gradient in prolactin concentration with increasing number of children, similar to the results of some 10,11,13 but not all 9,12,14 studies. In one of the studies with an observed gradient, the difference between nulliparous and uniparous was greater than between subsequent number of children.…”
Section: Discussionsupporting
confidence: 79%
“…9 In the other 2 studies, the change in prolactin levels with each child was relatively small (<1 ng/mL), similar to what we observed with a continuous variable, and may have been statistically significant given the large sample sizes (n 5 4,550 and 2,119). 12,14 While pregnancy appears to decrease prolactin levels, an additional benefit of earlier age at first birth has not been shown in the few prior studies of this association [11][12][13][14] or in the current study.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…These results are consistent with previous observations on long-term effects of a first pregnancy on the hormonal environment. Reductions in hormone concentrations after a first full-term pregnancy were reported in both pregnant and nonpregnant states for estrogens in serum (16,25,26,35,36) and breast fluid (37), serum adrenal androgens dehydroepiandrosterone and sulfated dehydroepiandrosterone (38), serum hCG (39)(40)(41)(42), and prolactin (13,43). Musey et al have described significant long-term decreases after a first pregnancy in basal and perphenazine-stimulated levels of prolactin (13), as well as with dehydroepiandrosterone and sulfated dehydroepiandrosterone (38).…”
Section: Discussionmentioning
confidence: 99%